121k views
7 votes
Help me ohhhhhhhhhhhhhhh

Help me ohhhhhhhhhhhhhhh-example-1

2 Answers

4 votes

Answer:

The solution is 6-->4-->9-->7-->1

Step-by-step explanation: h

User Pavel Bely
by
5.4k points
2 votes

Answer:

g(-3)+13= -8

f(h+9)=2h+12

f(7)+9=17

f(3)+g(2)=-6

3(g(b)+2)=3b-6b²+6

Explanation:

f(x)=2x-6 and g(x)=x-2x²

g(-3)+13

((-3)-2(-3)²)+13

(-3-2(9))+13

-3-18+13

-8

f(h+9)

2(h+9)-6

2h+18-6

2h+12

f(7)+9

(2(7)-6)+9

14-6+9

17

f(3)+g(2)

(2(3)-6)+(2-2(2²))

(6-6)+(2-2(4))

0+2-8

-6

3(g(b)+2)

3((b-2b²)+2)

3b-6b²+6

User Redax
by
5.2k points